Depth-dependent variation of archaeal ether lipids along soil and peat profiles from southern China: Implications for the use of isoprenoidal GDGTs as environmental tracers. (February 2019) - Yang, Huan; Xiao, Wenjie; Słowakiewicz, Mirosław; Ding, Weihua; Ayari, Asma; Dang, Xinyue; Pei, Hongye
Highlights: Archaeal isoGDGTs in peat and soil depth profiles investigated. %Cren and Methane Index (MI) progressively decreased with depth in peats and soils. Ring Index (RI) of OH-GDGTs correlated with the GDGT-0/crenarchaeol ratio in peats. Anaerobic archaea-derived isoGDGTs increase with depth in peat and soil profiles. Abstract: The distribution of archaeal isoprenoidal glycerol dialkyl glycerol tetraethers (isoGDGTs) has been increasingly used to characterize the archaeal community and to reconstruct palaeoenvironmental change. However, except for temperature, other environmental factors controlling the distribution of isoGDGTs remain to be explored. Environmental factors generally vary with depth along peat and soil profiles (PP and SP), which can provide unique opportunities to determine the impact of factors other than temperature on the distribution of archaeal ether lipids (AEL) in these settings. Here, we investigated the changes in AEL in two PPs and two red (ferralsol) SPs from southern China and determined the relationship of their distributions with peat and soil depth. The isoGDGT distribution in the two PPs and two SPs all show a significant dependence on depth. Crenarchaeol, which is likely to be produced by Thaumarchaeota, dominates in the upper parts of PPs and SPs, whereas GDGT-0 or isoGDGTs containing cyclopentyl moieties are the most abundant compounds in the deeper parts of these profiles. The change in the AEL distribution can be best characterized by %Cren (the proportion of crenarchaeol in total isoGDGTs) and MI (Methane Index), which are closely related to the water content in PPs and SPs. This suggests that %Cren and MI have potential for tracing the water content and, in turn, the redox conditions in paleosols and peats. The most remarkable differences in the AEL between PPs and SPs are the increased abundance of AEL, e.g., GDGT-5 (isoGDGTs with five cyclopentyl moieties), butanetriol dialkyl glycerol tetraethers (BDGTs), H-shaped isoGDGTs, methylated H-shaped isoGDGTs (Me-H-GDGTs) and the decreased abundance of hydroxylated isoGDGTs (OH-GDGTs) with depth in the two PPs, whereas these lipids are absent from the two SPs. This implies that the former group of lipids is likely derived from anaerobic archaea whereas OH-GDGTs and crenarchaeol are primarily of Thaumarchaeotal origin. The response of AEL to in situ environmental variables in the PPs and SPs reveals that the living archaea reside in the deep SPs and PPs and thus caution should be taken when applying these lipids to the high-resolution palaeoenvironmental reconstructions.